2022
DOI: 10.3390/biomimetics7020080
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Adhesive Performance of a Biomimetic Goat Hoof Track Shoe Pattern

Abstract: In this paper, reverse engineering technique was employed to extract the ridges of the hoof ball contour, and hoof ball tissue structure was analyzed based on the bionic prototype of goat hooves. The quantified geometric features were used to design the bionic track shoe pattern, which can enhance its adhesive performance and solve the problem that agricultural tracked vehicles in hilly and mountainous areas are prone to slip due to poor adhesive performance. The monolithic structure of the biomimetic goat hoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Through measurement and calculation, the soil density was 1330 kg/m 3 , the elastic modulus was 10 MPa, the Poisson’s ratio was 0.33 [ 20 ], the internal friction angle was 28.85°, and the cohesion was 44.08 kPa.…”
Section: Simulation Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Through measurement and calculation, the soil density was 1330 kg/m 3 , the elastic modulus was 10 MPa, the Poisson’s ratio was 0.33 [ 20 ], the internal friction angle was 28.85°, and the cohesion was 44.08 kPa.…”
Section: Simulation Testmentioning
confidence: 99%
“…The adhesion effect of the biomimetic sand-climbing wheel-surface was obviously higher than that of a conventional sand-climbing wheel-surface. Zhang [ 20 ] used reverse engineering technology to extract the contour line of the goat hoof-ball and analyzed the hoof-ball organization structure, designing the biomimetic goat-hoof track pattern by using the macroscopic features and microscopic characteristics of the goat hoof-ball. In addition, the adhesion performance of the imitation goat-hoof track pattern with that of the common single-line track pattern was compared.…”
Section: Introductionmentioning
confidence: 99%
“…16 It is well-known that numerical simulations and experiments are an essential approach to examining the drag-reduction characteristic of fish. 17,18 Diez et al 19 used the Realizable k-ε turbulence model to simulate the shark shape and obtained the model's drag coefficient, lift coefficient, and velocity field of the model in the flow field. Li et al 20 scanned the tuna to acquire the shape parameters of the tuna, facilitating the completion of structural modeling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The preliminary study of the research group [29][30][31] found that several functional parts evolved by goats can adapt to the unstructured environment, showing strong adhesion and passing ability. Therefore, in this article, the goat was used as an experimental object, and the QTM gait analysis system was used to collect the three-dimensional force changes of the goat gait and hoof bottom under multi-slope.…”
Section: Introductionmentioning
confidence: 99%